2005
DOI: 10.6090/jarq.39.275
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Xanthomonas oryzae pv. oryzae Suggests Contribution of Large Numbers of Effector Genes and Insertion Sequences to Its Race Diversity

Abstract: The plant-pathogenic prokaryote Xanthomonas oryzae pv. oryzae (Xoo) causes bacterial blight, one of the most important diseases of rice. The bacterium is a model organism for the analysis of plant-pathogen interaction, because more than 30 races differing in virulence and 25 resistance genes in rice have been reported to date. We present here the complete genome sequence of Xoo strain MAFF 311018. The size of the genome was 4,940,217 bp, in a single circular chromosome. The genome structure of Xoo MAFF 311018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
180
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(185 citation statements)
references
References 39 publications
(55 reference statements)
1
180
0
3
Order By: Relevance
“…In addition, R gene-mediated Xoo resistance accompanies the suppression of auxin signaling. A search of the amino acid sequences of Pseudomonas syringae pv syringae iaaH and iaaM (Mazzola and White, 1994) against the putative encoding products of the Xoo (strains KACC10331 and MAFF311018) whole genome sequence (Lee et al, 2005;Ochiai et al, 2005) did not reveal any homologous sequence. We then searched databases and found that Xoo carries NIT proteins (National Center for Biotechnology Information protein database accession numbers AAW74756, AAW74754, and YP_200139), which may contribute to the accumulation of IAA.…”
Section: Xoo Infection Induces Endogenous Synthesis Of Iaa In Ricementioning
confidence: 99%
“…In addition, R gene-mediated Xoo resistance accompanies the suppression of auxin signaling. A search of the amino acid sequences of Pseudomonas syringae pv syringae iaaH and iaaM (Mazzola and White, 1994) against the putative encoding products of the Xoo (strains KACC10331 and MAFF311018) whole genome sequence (Lee et al, 2005;Ochiai et al, 2005) did not reveal any homologous sequence. We then searched databases and found that Xoo carries NIT proteins (National Center for Biotechnology Information protein database accession numbers AAW74756, AAW74754, and YP_200139), which may contribute to the accumulation of IAA.…”
Section: Xoo Infection Induces Endogenous Synthesis Of Iaa In Ricementioning
confidence: 99%
“…The genomic sequences are available for three strains of Xoo and one strain of Xoc (Lee et al, 2005;Ochiai et al, 2005;Lu et al, 2008;Salzberg et al, 2008). The full complement of TAL T3 effectors are now known for two strains of Xoo and one strain of Xoc, and both pathogens are unusual due to the high number of TAL effector genes within their individual genomes.…”
Section: Implication Of Interaction Between T3 Effectors and The Corrmentioning
confidence: 99%
“…At the same time, two lines of evidence indicate that strains of Xoo could defeat Xa27. First, avrXa27 is present in a single copy, at least in the two strains that have been examined; therefore, simple loss or mutation of the gene converts incompatible strains to compatible strains on plants with Xa27 (Gu et al, 2005;Ochiai et al, 2005). Second, mutation of avrXa27 in the strain PXO99 A converts PXO99…”
Section: Implication Of Interaction Between T3 Effectors and The Corrmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic resources available for distribution to researchers include strains of Xanthomonas oryzae pv. oryzae 4 and Mesorhizobium loti 3 , the entire genome sequences of which have been determined.…”
Section: Introductionmentioning
confidence: 99%